A Human 2D Primary Organoid-Derived Epithelial Monolayer Model to Study Host-Pathogen Interaction in the Small Intestine - Roodsant, Thomas; Navis, Marit; Aknouch, Ikrame; Renes, Ingrid B.; van Elburg, Ruurd M.; Pajkrt, Dasja; Wolthers, Katja C.; Schultsz, Constance; van der Ark, Kees C. H.; Sridhar, Adithya; Muncan, Vanesa (Frontiers in Cellular and Infection Microbiology, 2020)
Gut organoids are stem cell derived 3D models of the intestinal epithelium that are useful for studying interactions between enteric pathogens and their host. While the organoid model has been used for both bacterial and viral infections, this is a closed system with the luminal side being inaccessible without microinjection or disruption of the organoid polarization. In order to overcome this and simplify their applicability for transepithelial studies, permeable membrane based monolayer approaches are needed. In this paper, we demonstrate a method for generating a monolayer model of the human fetal intestinal polarized epithelium that is fully characterized and validated. Proximal and distal small intestinal organoids were used to generate 2D monolayer cultures, which were characterized with respect to epithelial cell types, polarization, barrier function, and gene expression. In addition, viral replication and bacterial translocation after apical infection with enteric pathogens Enterovirus A71 and Listeria monocytogenes were evaluated, with subsequent monitoring of the pro-inflammatory host response. This human 2D fetal intestinal monolayer model will be a valuable tool to study host-pathogen interactions and potentially reduce the use of animals in research.